SOLVENT FREE SYNTHESIS OF CHALCONE AS ANTIBACTERIAL SUBSTANCE - Susy Yunita Prabawati; Arifah Khusnuryani; Khamidinal Khamidinal (UNIVERSITAS SEBELAS MARET (UNS), 2017)
The aims of this study was to synthesize a compound of 3-methoxy-4-hydroxychalcone through Claisen-Schmidt condensation with grinding technique (solvent-free). Vanillin, acetophenone and 60 % NaOH catalyst used in this synthesis. Characterization of products was done with a spectrophotometer FTIR and 1H-NMR spectrometer. The product was obtained as a orange solid which has a melting point at 58 - 59 ˚C. Identification of the product by IR spectrophotometer showed the absorption of C=C in the wavenumber of 1496.76 cm-1 which confirmed that the hydration reaction of chalcone had occurred. Analysis using 1H-NMR spectrometer also showed the proton of the CH=CH appearing on chemical shift (δ) 7.99 ppm. The antibacterial activity test showed that the compounds of 3-methoxy-4- hydroxychalcone has a potential as an antibacterial against bacteria E. coli and B. subtilis.